Environmental Quality in OfficesEnvironmental Quality in Offices, by VischerJacqueline C.. New York: Van Nostrand Reinhold, 1989, 250 pp., $35.95, cloth. - Kulik, Carol T. (Academy of Management Review, 1990)
The article reviews the book ?Environmental Quality in Offices,? by Jacqueline C. Vischer.